Study on impact factors of small- and medium-span bridges under the special-purpose vehicle load. (September 2022) - Huang, Pingming; Wang, Junfeng; Han, Wanshui; Yuan, Yangguang
Abstract: To promote the infrastructure-construction and economic development, special-purpose vehicles (SPVs) to transport large indivisible loads are increasingly appearing on highway bridges, of which most are oversized and overweight. Dynamic impact of moving vehicles on bridges is an important and long-standing issue in the design and evaluation of bridges. The dynamic impact factor (IM) of SPVs on highway bridges is usually ignored or overestimated for the response of internal forces and safety assessments, which has been a barrier to the permit checking of SPVs. So, this paper studied the dynamic impact factors of small- and medium-span bridges under the special-purpose vehicle load. First, the characteristics of overweight SPVs load larger than 80T in one province of China is analyzed and five typical SPVs based on wheelbase distribution and market surveys were summarized. Then, an SPV-bridge coupled system was introduced. Dynamic model of SPVs and the spatial roughness models of bridge deck based on the wheel track correlation principle were established. Finally, effects of bridge type, span composition, vehicle speed, vehicle type, and road grade on the IMs are examined. The recommended IMs of average road condition (class C) are proposed for different bridge types and internal forces based on mathematical statistics and extreme value analysis. The results of this study can be used to scientifically evaluate bridges under SPVs loads and revise specifications.